Effects of the sequential implantation of Mg and N ions into GaN for p-type doping. (12th October 2021) - Sakurai, Hideki; Narita, Tetsuo; Kataoka, Keita; Hirukawa, Kazufumi; Sumida, Kensuke; Yamada, Shinji; Sierakowski, Kacper; Horita, Masahiro; Ikarashi, Nobuyuki; Bockowski, Michal; Suda, Jun; Kachi, Tetsu
Abstract: The sequential implantation of Mg and N ions into GaN was investigated using conventional rapid thermal annealing and ultra-high-pressure annealing (UHPA). In cathodoluminescence, the green luminescence related to nitrogen vacancies (VN s) was mostly suppressed at the Mg/N ratio of 0.5–1.0, whereas the donor–acceptor pair (DAP) emission as a signature of Mg acceptors was maintained high. The excess N implantation reduced the DAP emission through the formation of nonradiative recombination centers. The combined process of optimal Mg/N implantation and UHPA at 1673 K improved ohmic contacts by increasing Mg concentration and suppressing VN s near the surface.